Enemies or good neighbors? No indication of spatial or temporal avoidance between two sympatric South American canids. (28th March 2022) - Di Bitetti, M. S.; Iezzi, M. E.; Cruz, P.; Cirignoli, S.; Varela, D.; De Angelo, C.
Abstract: Niche partitioning is a common mechanism by which sympatric mammal carnivore species mitigate competition and achieve coexistence. This ecological process is usually measured along three axes: diet, space, and time. The Pampas fox ( Lycalopex gymnocercus ) and the crab‐eating fox ( Cerdocyon thous ) have similar morphologies and diets and share a wide area of sympatry in South America. We conducted a large camera‐trap survey ( 25 000 km 2, 234 stations, 10 494 camera‐trap days) in the subtropical savannas of Argentina to understand if the crab‐eating fox and the Pampas fox have a competitive coexistence, which would be evidenced by spatial and temporal avoidance. We predicted that the smaller and less social Pampas fox would avoid, either spatially or temporally, the presumably dominant crab‐eating fox. To study habitat associations, we used single‐species occupancy models. We used two‐species occupancy models to assess if the Pampas fox has a lower probability of occurrence ( ψ ) or detection ( p ) at locations occupied by the crab‐eating fox. We used circular statistics to evaluate if the Pampas fox becomes more diurnal in areas with high ψ of the nocturnal crab‐eating fox. These foxes showed different habitat associations. The Pampas fox had lower ψ in forest habitat. The crab‐eating fox had higher ψ at locations with more wetlands. Both foxes had higher ψ at locations with cattle. The ψ and p of the Pampas fox were not negatively affected by those of the crab‐eating fox, and there was no indication of spatial avoidance. Contrary to our prediction, the Pampas fox did not become more diurnal at locations with high ψ of the crab‐eating fox. The coexistence of these species seems to be facilitated by their similarity in body weight, which reduces the chances of intraguild killing, coupled with their divergent niches, which is evidenced in their different habitat preferences within shared landscapes. Abstract : The Pampas fox and the crab‐eating fox have similar diets and are sympatric in South America. No spatial and temporal avoidance between these species was found in northeastern Argentina using camera‐trap data in two‐species occupancy models and circular statistics. Species coexistence seems to be facilitated by their divergent niches and the low chances of intraguild killing.